Salvador Dalí Pincel Pixel: uma análise da obra "Gala a Olhar o Mar Mediterrâneo que, a Dezoito Metros de Distância se Transforma no Retrato de Abraão Lincoln", 1975 - Andrade, Léia Cláudia da Silva (2009)
Contemporary society constantly lives under a flow of images which invades the visual field all the time. Considering this fact, the act of seeing can produce uncertain conditions of interpretations and articulations of the images. Analysing the paintings of Salvador Dalí, Gala Looking to the Mediterranean Sea that, in Eighteen meters away, becomes the portrait of Abraham Lincoln, 1975, will guide us to a path conducted by the act of seeing and also comprehending what has just been seen. This reasearch proposes a deep analysis of the artist Salvador Dalí, as well as dialogue between the fields of art, technology, cultural history and related whenever possible with the pixels of digital images.